Environmental microbiology - Sharma, P. D. (Alpha Science International, 2005)
Contents of the book is: Environment, public health, industry and agriculture. This book attempts to bring all scattered material on applied effects of microorganisms on environment, human health and welfare together in the form of a complete book on environmental microbiology. Besides students, the book would interest those inclined to learn how microbes help maintain the quality of environment and balance of nature.